Kebangkitan Yesus Menurut Injil Lukas 24:1-49 dan Implikasinya Bagi Gereja Masa Kin - Hironimus Resi; Teresia Noiman Derung (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
The resurrection of Jesus holds significant importance for Christians, as it represents his triumph over sin, death, and darkness, offering the promise of eternal life to believers. This event is central to the Christian faith, symbolizing the transformative power it holds. While the Church is tasked with carrying out its five pillars, many struggle to grasp and apply these responsibilities in the modern world. This article delves into the meaning of Jesus' resurrection, as described in Luke 24:1-49, and its relevance for the Church today. Utilizing a qualitative approach with a literature study, the findings reveal that Jesus' resurrection is characterized by an empty tomb and his repeated appearances to the disciples. The resurrection signifies the Church's mission to proclaim this event, transcend spiritual existence into eternity, and demand faithfulness in God. The implications of Jesus' resurrection for the Church today can be fulfilled through the five tasks of the Church: communion or koinonia, ministry or diakonia, preaching or kerygma, sanctification or liturgia, and witness or martyria. Demonstrating faithfulness in these duties serves as a testament to the proclamation of Jesus' resurrection.